Gender-related mortality for HIV-infected patients on highly active antiretroviral therapy (HAART) in rural Uganda - Alibhai, Arif; Kipp, Walter; Senthilselvan, Ambikaipakan; Konde-Lule, Joseph; Okech-Ojony, Joa; Rubaale, Tom (International journal of women's health, 2010)
The purpose of this study was to examine gender differences in mortality for human immunodeficiency virus (HIV) patients in rural Western Uganda after six months of highly active antiretroviral therapy (HAART). Three hundred eighty five patients were followed up for six months after initiating HAART. Statistical analysis included descriptive, univariate and multivariate methods, using Kaplan–Meier estimates of survival distribution and Cox proportional hazards regression. Mortality in female patients (9.0%) was lower than mortality in males (13.5%), with the difference being almost statistically significant (adjusted hazard ratio for females 0.55; 95% confidence interval [CI]: 0.28–1.07; P = 0.08). At baseline, female patients had a significantly higher CD4+ cell count than male patients (median 147 cells/μL vs 120 cells/μL; P < 0.01). A higher CD4+ cell count and primary level education were strongly associated with better survival. The higher CD4+ cell count in females may indicate that they accessed HAART services at an earlier stage of their disease progression than males. A borderline statistically significant lower mortality rate in females shows that females fare better on treatment in this context than males. The association between lower mortality and higher CD4+ levels suggest that males are not accessing treatment early enough and that more concerted efforts need to be made by HAART programs to reach male HIV patients.
Keywords: antiretroviral treatment; gender; rural